Supplementary material to the book chapter "Facility Location Modeling in Supply Chain Network Design: Current State and Emerging Trends" - Yasel José Costa Salas; Teresa Melo (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2021)
Facility location decisions play a critical role in the design of supply chain networks. This chapter outlines key features of facility location problems and their integration with various logistic operations in the context of network (re)design. Modeling approaches and solution methods are also discussed for these challenging combinatorial optimization problems. In addition, we examine five emerging trends that will continue to drive research in this area, namely, sustainable development, the transition to a circular economy, data source-related issues, disruptive events and resilience, and omnichannel distribution in the retail sector. We review and classify recent contributions, identify research gaps, and provide directions for future research.
Additional information: This document contains the supplementary material to the following book chapter: Y. Costa, T. Melo, Facility Location Modeling in Supply Chain Network Design: Current State and Emerging Trends, In: The Palgrave Handbook of Supply Chain Management, J. Sarkis (ed.), Heidelberg, 2022.
Keywords: 650; Facility location; Sustainable network design; Circular economy; Data scarcity; Resilience; Omnichannel